“Things can change in a day”: - Khandakar Ashraful Islam; Shirin Akter (Crossings, 2020)
In both of her novels, Arundhati Roy focuses on specific fatal incidents – either deliberate or accidental – which have catastrophically changed the lives of the major characters, including the children. In The God of Small Things, the unexpected death of Sophie Mol and brutal killing of Velutha exposed those matrices of oppression which, lying unchallenged apart from jeopardizing Ammu and Velutha, problematized the psychic development of Rahel and Estha. Likewise, in The Ministry of Utmost Happiness, Anjum’s deadly experience in the Gujarat massacre, the brutal rape of Revathy, and the killing of Miss Jebeen in Kashmir shed light on those dreadful socio-political extremities, which ostensibly beckon an endangered future for the generation to come. Focusing on Roy’s novels, this paper attempts to exhibit how the predominance of the socio-political upheavals has not only changed the lived experience of the child characters in a cataclysmic way, but also exposed them to a world of cruelty, injustice, and futurelessness.